A Study on the Development of Agriculture and Changing Cropping Pattern - Anwar, Khalid; Hussain, Shagufta (Journal of Commerce and Trade, 2015)
In studying the various facets of agriculture, the first and the foremost thing to know about is regarding the pattern crops, the production of various crops, and the productivity of land and the inputs in respect of these crops. A recent development of considerable importance is the emergence of foodgrains surpluses. A variety of crops are grown in India. The single most important element in crop production strategy in the post-green revolution period is improved agricultural technology. This technology is in the form of high yielding plant varieties, intensive cultivation, greater use of fertilizers, increased irrigation and better tecniques for ploughing, harvesting and plant protection. High yielding varieties have been developed for a number of crops but their impact on production, productivity and costs varies across crops and regions. The success of the state water policy will depend entirely on the development and maintenance of general consensus and commitments to its underlying principles and objectives.